Small teaching, big results: Leveraging department chairpersons to improve teaching and learning - Lori Ann Mumpower (To Improve the Academy)
The Center for Teaching and Learning Excellence at Embry-Riddle Aeronautical University (ERAU) created a Small Teaching Challenge, leveraging department chairpersons to encourage faculty adoption of evidence-based, small teaching practices. Inspired by James Lang’s Small Teaching (2016) and previous collaborations with department chairpersons, the Small Teaching Challenge reached 12 out of 18 departments and 29% of full-time faculty. Post-challenge survey results revealed 94% of participating faculty would likely continue the small teaching practices, and 100% of department chairpersons would participate again. The article reviews literature on department chairpersons’ contributions to faculty development, program details, results, and implications for educational developers.